Students' and Teachers' Attitudes towards the Significance of Learning Foreign Languages for Specific Purposes - Nataša Z. Janković; Zorica B. Savić Nenadović; Marina S. Cvetković (University of Belgrade, Teacher Education Faculty, 2019)
In the modern-day world, developing language competences in general, and the competences for using foreign languages for specific purposes in particular, has become a prerequisite for the professional, personal, and cultural development of the young population. In Serbia, despite the ongoing curricular reforms and a declarative determination of educational authorities to follow modern European trends in education, the changes introduced in the area of foreign language teaching at all levels of education can be detrimental to both professional and cultural development of young people. The aim of this research is to present and analyse the opinions of students and university teachers about the significance of learning foreign languages, particularly of foreign languages for specific purposes. We conducted empirical research using a survey as the technique and a questionnaire as the research instrument. The qualitative and quantitative analyses of the data obtained from the sample of 1,590 students and 92 foreign language teachers at the University of Belgrade and other state and private universities in the country demonstrate that the majority of the students and teachers fully realise the importance of learning foreign languages, and in particular of foreign languages for specific purposes, for their professional development, career advancement, and broadening their cultural horizons. Both groups of respondents agree that students should learn more than one foreign language and that the number of foreign language lessons should be increased at all levels of education.